Intrinsic Facet‐Dependent Reactivity of Well‐Defined BiOBr Nanosheets on Photocatalytic Water Splitting - Shi, Ming; Li, Guanna; Li, Jianming; Jin, Xu; Tao, Xiaoping; Zeng, Bin; Pidko, Evgeny A.; Li, Rengui; Li, Can (Angewandte Chemie International Edition, 2020)
Surface atomic arrangement and coordination of photocatalysts highly exposed to different crystal facets significantly affect the photoreactivity. However, controversies on the true photoreactivity of a specific facet in heterogeneous photocatalysis still exits. Herein, we exemplified well‐defined BiOBr nanosheets dominating with respective facets, (001) and (010), to track the reactivity of crystal facets for photocatalytic water splitting. The real photoreactivity of BiOBr‐(001) were evidenced to be significantly higher than BiOBr‐(010) for both hydrogen production and oxygen evolution reactions. Further in situ photochemical probing studies verified the distinct reactivity is not only owing to the highly exposed facets, but dominated by the co‐exposing facets, leading to an efficient spatial separation of photogenerated charges and further making the oxidation and reduction reactions separately occur with different reaction rates, which ordains the fate of the true photoreactivity. Intrinsic facet‐dependent photoreactivity: It is demonstrated that the spatial separation of photogenerated charges between top and lateral facets of BiOBr nanosheets dominates the intrinsic facet‐dependent photoreactivity, and not the commonly recognized highly exposed active facets.